PENERAPAN SERVICE EXCELLENT OLEH CUSTOMER SERVICE PADA UNIVERSITAS ISLAM SYEKH YUSUF TANGERANG - Yoman, Mad; Pradesti, Ajeng (DIALEKTIKA KOMUNIKA: Jurnal Kajian Komunikasi dan Pembangunan Daerah, 2023)
This research aims to describe the application of excellent service by Syekh-Yusuf Islamic University to prospective new students. Excellent service focuses on CS abilities, attitudes, appearance, actions, attention and responsibilities in serving customer communications or in this case prospective new students. This research uses a qualitative approach with a case study type. The results of the research show that the excellent assessment at the Syekh-Yusuf Islamic University has been carried out well, but must continue to be improved so that the satisfaction of prospective new students can be achieved well. And training is needed to improve knowledge, skills and appearance in providing excellent service to prospective new students.